2021
DOI: 10.3389/fnins.2021.695138
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Voluntary Exercise on Stroke Recovery

Abstract: Stroke treatment is limited to time-critical thrombectomy and rehabilitation by physiotherapy. Studies report beneficial effects of exercise; however, a knowledge gap exists regarding underlying mechanisms that benefit recovery of brain networks and cognition. This study aims to unravel therapeutic effects of voluntary exercise in stroke-induced mice to develop better personalized treatments. Male C57Bl6/JOlaHsd mice were subjected to transient middle cerebral artery occlusion. After surgery, the animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The effects of post-stroke voluntary movements on neuronal regeneration and repair have been shown to be related to the upregulation of growth-associated protein 43 and neurotrophin 3 ( Xing et al, 2018 ). A recent study reported that early commencement of VE post-stroke improved cerebral blood flow, vascular quality, and brain functions such as connectivity and motor abilities ( Lohkamp et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of post-stroke voluntary movements on neuronal regeneration and repair have been shown to be related to the upregulation of growth-associated protein 43 and neurotrophin 3 ( Xing et al, 2018 ). A recent study reported that early commencement of VE post-stroke improved cerebral blood flow, vascular quality, and brain functions such as connectivity and motor abilities ( Lohkamp et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, he highlighted that better experimental design leads to maximum quality of data from the animals that need to be used, and ensures that they are not wasted due to insufficient 'experimental power'. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Designing your in vivo studies while supporting the 3Rs…”
Section: Novel Biomarkers Animal Welfare and Data Reproducibility In ...mentioning
confidence: 99%
“…It is a non-invasive, low-cost, personalized, and most importantly, a physiologically natural way of gaining wellness. Mounting evidence indicates the positive effect of PE as a non-pharmacological approach to prevent cognitive decline in elderly populations [13][14][15][16]. Major mechanisms proposed to account for this effect are the following [17,18]: first, daily exercise helps maintain cerebral blood flow, which is indispensable for healthy brain function; second, it mitigates comorbidities (e.g., hypertension, hyperlipidemia, diabetes, obesity, atherosclerosis), which can increase the risk of poor cerebral blood flow; third, it stimulates the expression of neurotrophic factors, such as insulin-like growth factor 1 (IGF-1), brain-derived neurotrophic factor (BDNF), vascular endothelial growth factor (VEGF) and fibroblast growth factors (FGFs) including FGF2; fourth, it promotes clearance of amyloid-beta via glymphatic and meningeal lymphatic systems [19,20]; and fifth, it suppresses activation of neurotoxic inflammatory molecules (e.g., tumor necrosis factor-alpha, interleukin-6, and interleukin-1beta) [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, slowing demyelination or promoting remyelination of the brain could represent some early therapeutic strategies for AD, before the occurrence of significant neurodegeneration. While pharmacotherapies targeting myelination have not been established yet, recent studies have demonstrated that PE can help myelinate brains [15,[34][35][36], suggesting a novel PE-based mechanism for counteracting cognitive decline in AD. In support of this view, some reports have indicated the therapeutic potential of PE to promote remyelination in demyelinating disorders, such as MS and central pontine myelinolysis [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%